Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s12913-022-08746-0
|View full text |Cite
|
Sign up to set email alerts
|

Development of an acute medical unit to optimize patient flow and early discharges in a tertiary care hospital in the United Arab Emirates

Abstract: Background Hospitals worldwide are seeing an increased number of acute admissions, with resultant emergency department (ED) crowding and increased length of stay (LOS). Acute Medical Units (AMUs) have developed throughout the United Kingdom and other Western countries to reduce the burden on EDs and improve patient flow. Limited information is available on AMUs in the Middle East. The purpose of this study is to describe the development of the first AMU in the United Arab Emirates (UAE) for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…A recent study demonstrated that implementing an ED-based ICU resulted in a 15.4% reduction in mortality for critically ill patients compared to traditional ED management [44]. The implementation of acute units was associated with decreased ICU and hospital LOS, lower rates of ICU admission [45 ▪ ], and reductions in the number of patients boarding in the ED [46 ▪ ]. However, the implementation of RCUs presents challenges.…”
Section: Emergency Department Solutionsmentioning
confidence: 99%
“…A recent study demonstrated that implementing an ED-based ICU resulted in a 15.4% reduction in mortality for critically ill patients compared to traditional ED management [44]. The implementation of acute units was associated with decreased ICU and hospital LOS, lower rates of ICU admission [45 ▪ ], and reductions in the number of patients boarding in the ED [46 ▪ ]. However, the implementation of RCUs presents challenges.…”
Section: Emergency Department Solutionsmentioning
confidence: 99%